Effect of nitrate and sulfate coexistence on hydrogen autotrophic reduction of antimonate (Sb(V)) and microbial community structures. (December 2022) - Wan, Dongjin; Wang, Yiduo; Liu, Yang; Gu, Mengqi; Liu, Yongde; Xiao, Shuhu; He, Qiaochong
Abstract: Hydrogen autotrophic bioreduction of antimonate (Sb(V)) to antimonite (Sb(III)) is an alternative approach for removing antimony (Sb) from water. This study investigated Sb(V) reduction kinetics and the effects of various parameters on the Sb(V) removal performance in a hydrogen autotrophic reaction system (HARS). Sb(V) reduction in the HARS was well fitted to the Michaelis-Menten model, showing a positive correlation between the reaction rate and biomass. The maximum specific substrate removal rates were 0.29–4.86 and 6.82–15.87 mg Sb(V)/(g·VSS·h) at initial Sb(V) concentrations of 500 μg/L and 10 mg/L, respectively. Coexisting nitrate significantly inhibited Sb(V) reduction, and the inhibition intensified with increasing nitrate concentration. However, coexisting sulfate had a positive effect on Sb(V) reduction, and the sulfate effectively enhanced total antimony (TSb) removal performance by generating sulfide from sulfate reduction. Illumina high-throughput sequencing technology was used to determine the changes in microbial community structure during different periods in the HARS, revealing the effects of co-existing ions on the dominant Sb(V) reducing bacteria. In the HARS, Longilinea and Terrimonas were the dominant genera in the presence of nitrate, and Longilinea was the dominant genus in the presence of sulfate, at initial Sb(V) concentration of 500 μg/L. When the concentration of Sb(V) was 10 mg/L, Longilinea and Thauera were the dominant genus in the HARS for treating water co-polluted with nitrate and sulfate, respectively. These results provide a theoretical basis of the application of HARS for the bio-remediation of Sb(V) contaminated water. Graphical abstract: Image 1 Highlights: Antimonate reduction kinetics at different concentration was fitted by Michaelis-Menten model. Nitrate significantly inhibited antimonate reduction by electron donor competition. Sulfate enhanced total antimony removal performance by sulfate reduction to sulfide. Co-existing ions led to the changes in dominant antimonate reducing bacteria.